2011
DOI: 10.1088/0031-9155/56/4/008
|View full text |Cite
|
Sign up to set email alerts
|

Surface dosimetry for breast radiotherapy in the presence of immobilization cast material

Abstract: Curative breast radiotherapy typically leaves patients with varying degrees of cosmetic damage. One problem interfering with cosmetically acceptable breast radiotherapy is the external contour for large pendulous breasts which often results in high doses to skin folds. Thermoplastic casts are often employed to secure the breasts to maintain setup reproducibility and limit the presence of skin folds. This paper aims to determine changes in surface dose that can be attributed to the use of thermoplastic immobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 17 publications
(26 reference statements)
0
28
0
Order By: Relevance
“…A special design of MOSFET detector known as MOS kin for its dosimetry capabilities at skin surface and interfaces 26 , 27 , 52 , 53 , 54 , 55 , 56 , 57 , 58 was used in this study. MOS kins are real‐time detectors offering water‐equivalent effective depth (WED) of measurement of 0.02 or 0.07 mm, depending on type, developed at the Centre for Medical Radiation Physics (CMRP), University of Wollongong, Australia.…”
Section: Methodsmentioning
confidence: 99%
“…A special design of MOSFET detector known as MOS kin for its dosimetry capabilities at skin surface and interfaces 26 , 27 , 52 , 53 , 54 , 55 , 56 , 57 , 58 was used in this study. MOS kins are real‐time detectors offering water‐equivalent effective depth (WED) of measurement of 0.02 or 0.07 mm, depending on type, developed at the Centre for Medical Radiation Physics (CMRP), University of Wollongong, Australia.…”
Section: Methodsmentioning
confidence: 99%
“…Several groups have examined the effect of thermoplastic immobilization shells on surface dose for both photons and electrons and have concluded that they can significantly increase skin dose. 29,31,[50][51][52][53][54] Surface dose was found to decrease as the mask material was increasingly stretched which reduced the areal density and mask thickness (and reproducibility). For 6 MV photons, without stretching, the surface dose was 61% compared to 16% without a mask, but with stretching that increased the area of the mask by 125% or 525%, the surface dose changed to 48% or 29%, respectively.…”
Section: B3 Thermoplastic Shellsmentioning
confidence: 99%
“…The MOSFETs surface dose response increases with increasing beam obliquity. 19 Previous studies have utilized this MOSFET for in-field skin and surface dosimetry. 19,26 Also for rectal wall interface dosimetry 27 and for brachytherapy applications.…”
Section: Iic Mosfet Dosimetrymentioning
confidence: 99%
“…19 Previous studies have utilized this MOSFET for in-field skin and surface dosimetry. 19,26 Also for rectal wall interface dosimetry 27 and for brachytherapy applications. 24 The accuracy of the MOSFET, utilized for this study, for out-of-field dosimetry was assessed.…”
Section: Iic Mosfet Dosimetrymentioning
confidence: 99%
See 1 more Smart Citation